Semantic-functional features of repetition in the poetry of Taras Melnychuk - Тищенко, Зара Робертівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is sanctified to research of T. Y. Melnychuk. The features of functioning of repetition are certain as one of dominants of style of writer. After analyzing the specific manifestation of polysyndeton, anaphora, epiphora, epanaphora, rapitori, chiasm, refrain, full, paradigmatic and derivational repetitions and other forms of repetition. It`s discovered that repetetion is important, depicting and tekstotvirnij mean. Repeat the operation represents tne folk-song origins of linguistic creativity of poet. Evidence of a high level of artistic language of the poet, specific of his poetics is a masterful combination of different types and repeats that serves as closer ties of components verse. Poetic features movomyslennya most clearly manifested in stylistics-syntactic organization of individual morks of the author and the whole assembly.